Chemical Composition of the Essential oil of The Leaves of Pimenta diocia (L.) Merr. & Pimenta racemosa (Mill.) cultivated in Egypt and Evaluation of Their in-vitro Antioxidant and Antidiabetic Activities - Heba Abd-Elhady El-gizawy; Yasser Omar Mosaad; Naglaa Abd El Khalik Gobba; Mohammed Abdalla Hussein (International Journal of Phytomedicine, 2018)
The aim of the study is to identify and characterize the chemical composition of the essential oil of both leaves of Pimenta diocia (L.) Merr. and Pimenta racemosa (Mill.) as well as to evaluate their in-vitro antioxidant and anti-diabetic potency. Both leaves essential oil was analyzed by GC-MS analysis. Different in-vitro antioxidant tests were employed, namely, 1,1-diphenyl-2-picrylhydrazyl (DPPH), ferric thiocyanate (FTC), ferric reducing antioxidant power, thiobarbituric acid (TBA) and β-carotene-linoleate bleaching assay. Also, the present work aims to evaluate the α-amylase and α-glucosidase inhibition as well as glucose uptake by yeast cells of essential oils. Essential oil analysis of the leaves of Pimenta racemosa (Mill.) showed high amounts of eugenol (37.95%), β-Myrecene (21.01%), α-Pinene (17.82%), linalool (6.15%) and limonene (5.93%). GC-MS data of leaves essential oil revealed the presence of eugenol (30.17%), limonene (17.24), α-Pinene (16.78%), linalool (9.71), 1,8 cineole (8.31%) and β-myrecene (5.21%) . Pimenta diocia (L.) Merr. and Pimenta racemosa (Mill.) leaves essential oil having antioxidant effect using various methods. In most of the oil samples and assays the antioxidant activity was higher than the one revealed by the positive control BHT. Both plants essential oil showed potent inhibition of α-Amylase at concentration 2.00 mg as it was inhibited by (75 and 63 %); with IC50 (0.95 and 1.13); respectively as well as inhibition of α-glucosidase enzyme by (61.42 and 53.00%) with IC50 (3.17 and 4.25); respectively. Also the percentage of glucose uptake by Pimenta diocia (L.) Merr. and Pimenta racemosa (Mill.) leaves essential oil at 2.00 mg/ml in the presence of 25 mM glucose is (63.49% and 49.61%); respectively. Conclusion: the present study clearly identified the Egyptian chemotype of Pimenta diocia (L.) Merr. and Pimenta racemosa (Mill.) leaves essential oil, it also displayed safe and promising antidiabetic and antioxidant properties. Therefore the essential oil of both species can be utilized as a natural antioxidant and antidiabetic as well as health benefits.